- #1
negation
- 818
- 0
Case of a spring with a mass,m, that has been stretch beyond the equilibrium in the positive x direction.
mg + (-kx0) = 0
k = mg/x0
stretch:
F = mg+ [-k(x0+x1)] = mg-kx0-kx1
but since mg-kx0 = 0
F = 0-kx1 = ma
ma = -kx1
a = -kx1/m
How do I arrive at the corollary from a = - kx1/m to ω0 = SQRT[k/x]?
mg + (-kx0) = 0
k = mg/x0
stretch:
F = mg+ [-k(x0+x1)] = mg-kx0-kx1
but since mg-kx0 = 0
F = 0-kx1 = ma
ma = -kx1
a = -kx1/m
How do I arrive at the corollary from a = - kx1/m to ω0 = SQRT[k/x]?